2019
DOI: 10.1002/qre.2556
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance‐based reliability and optimization design of switched‐mode power supply

Abstract: Due to its high efficiency and low power consumption, switched‐mode power supply (SMPS) represents the development trend of the stabilized voltage power supply. However, tolerance has become one of the key factors in the design of SMPS because of the process fluctuation of electronic components, unstable input parameters of the circuit system, influence of working conditions and environment, and the effect of aging. In order to improve the reliability of SMPS and reduce the manufacturing cost, this paper propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this engineering case, a bridge system is taken as an example for verifying the reliability redundancy allocation optimization performance of different algorithms 41 . Figure 3 shows the reliability block diagram.…”
Section: Engineering Applications Of Dtpso In Reliability Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this engineering case, a bridge system is taken as an example for verifying the reliability redundancy allocation optimization performance of different algorithms 41 . Figure 3 shows the reliability block diagram.…”
Section: Engineering Applications Of Dtpso In Reliability Optimizationmentioning
confidence: 99%
“…In this engineering case, a bridge system is taken as an example for verifying the reliability redundancy allocation optimization performance of different algorithms. 41 Figure 3 shows the reliability block diagram. In addition, for reliability redundancy allocation, each unit in this system has only two states including normal and failure, moreover, the states of units are independent.…”
Section: Reliability Redundancy Allocation Optimizationmentioning
confidence: 99%
“…Choi [22] and others [23,24], is designed to narrow the gap between such real-world industrial uncertainties and deterministic optimization based on probabilistic theory. It has been observed that uncertainties such as tolerances that can occur in actual industrial processes can be reflected by considering the probability distribution of each design variable, and through this, it is possible to derive an optimal design solution that guarantees reliability [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this challenge, many scholars have applied machine learning 27,28 to improve the efficiency of structural reliability analysis. By integrating optimization design 29 and reliability analysis methodologies, 30,31 reliability metrics can be embedded into the design phase, 32,33 thus ensuring the reliability level of turbine shaft during the fatigue optimization design. 34 To enhance the life expectancy of a turbine shaft under CCF loading, this study proposes a fatigue reliability analysis and optimization design method.…”
Section: Introductionmentioning
confidence: 99%